Homochiral mono- and dinuclear SmIII complexes showing the effect of nuclearity on their photophysical properties. (17th June 2016) - Li, Xi-Li; Zhang, Xue-Li; Hu, Ming; Zhu, Cancan; Chen, Conghui; Wang, Ai-Ling
Graphical abstract: Using enantiopure bis-bidentate ligands, two mono- and dinuclear Sm III enantiomeric pairs have been synthesized, depending on the ratio of the reactants. The photophysical properties of the mononuclear Sm III enantiomers are superior to those of the dinuclear Sm III analogs, demonstrating that the Sm nuclearity has a considerable effect on their photophysical properties. Abstract: Using the enantiopure bis-bidentate ligands (−)/(+)-2, 5-bis(4, 5-pinene-2-pyridyl)pyrazine (L R /L S ), two mono- and dinuclear Sm III enantiomeric pairs with the formulae [Sm(dbm)3 L R / S ]·C2 H6 CO·H2 O ( R -1 and S -1 being the isomers containing the L R and L S ligands, respectively, and dbm = dibenzoylmethanate) and [Sm2 (dbm)6 L R / S ]·2H2 O ( R -2 and S -2 being the isomers containing the L R and L S ligands, respectively) have been synthesized and characterized by X-ray crystallography and spectroscopic technologies. The nuclearity of the complexes isolated depends on the ratio of the reactants. Circular dichroic (CD) spectra confirmed their chiroptical activities and enantiomeric natures. Measurement of the luminescence properties revealed that both the mono- and dinuclear Sm III complexes display the characteristic deep-red emissions of Sm III ions in the solid state. Notably, in contrast to the previously reported dinuclear Sm III complex based on a bis-β-diketonate ligand, whose emission intensity is much larger than that of the mononuclear analog, the intensity of the emission signal for the mononuclear complex R -1 is more than ten times larger than that of the dinuclear species R -2 . The reason for this phenomenon is elucidated in this work. Thus, our research results demonstrate that the Sm nuclearity has a considerable effect on the photophysical properties of Sm III mono-β-diketonate complexes, which is contrary to the observation in Sm III bis-β-diketonate complexes.